Enhanced Antibacterial Activity of Hydrophobic Modified Lysozyme Against Gram-Negative Bacteria Without Accumulated Resistance - Zhenhui Li; Song Lin; Mei Zhu; Xiaoman Liu; Xin Huang (Molecules)
Macromolecule bactericides present challenges such as low biocompatibility and not being biodegradable, so broad-spectrum bactericides without accumulated bacteria resistance are now in urgent demand all over the world. Lysozyme, a kind of wide-spread natural enzyme easily extracted from nature, has become attractive for agriculture and medicine use. However, Gram-negative bacterial strains are highly resistant to natural lysozymes, which limits their practical application. In this study, rather than directly modifying antibacterial-active substance with lysozyme, we show an effective way to improve antibacterial performance by altering the hydrophobic functional groups of natural lysozymes and synthesize a type of hydrophobic modified lysozyme (HML). Compared with other modification methods, the antibacterial performance has been increased by over 50%. We investigated its antibacterial mechanism against Gram-negative bacteria and showed that HML could be used to treat pathogenic bacteria without obvious accumulated resistance appearance, which is a great advantage over commercial antibiotics. Overall, it is anticipated that HML could be potentially applied to food safety, infection therapy, and enzyme-medicine applications.